Project management practices and implementation at Government and Private enterprises: Examining the Relationship between Project Management Practices and Building Construction Success (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Due to several reasons including lack of resources, poor planning, lack of time, lack of labor,and others, the majority of organizations have failed to finish their projects. Organizations use a variety offrameworks or recommendations to combat the current problems. A developing idea that establishes andupholds project management standards within an organization is the project management office (PMO).Despite the widespread adoption of project management in India's public sector, private companies havemostly stuck to tried-and-true practises. A descriptive survey approach was employed for this study. Thestudy's target population consisted of the 703 licensed architectural, quantity surveying, andengineering firms that were engaged in capital-intensive building construction projects. According to thestudy's findings, effective building construction was significantly and favorably related to resourceplanning, monitoring, top management support, and communication.